2016
DOI: 10.1038/nchem.2615
|View full text |Cite
|
Sign up to set email alerts
|

An infrared spectroscopy approach to follow β-sheet formation in peptide amyloid assemblies

Abstract: Amyloidogenic peptides and proteins play a crucial role in a variety of neurodegenerative disorders such as Alzheimer's and Parkinson's disease. These proteins undergo a spontaneous transition from a soluble, often partially folded form, into insoluble amyloid fibrils that are rich in β-sheets. Increasing evidence suggests that highly dynamic, polydisperse folding intermediates, which occur during fibril formation, are the toxic species in the amyloid-related diseases. Traditional condensed-phase methods are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
177
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 191 publications
(193 citation statements)
references
References 41 publications
7
177
0
3
Order By: Relevance
“…Again space constraints prevent the details from being given here. It was found that β-sheet onset was spectroscopically observed for both VEALYL and YVEALL with onset at n = 4 extending to n = 9 (the largest oligomer studied) but no β-sheet absorptions were observed for VELYAL in accordance of expectations from both IMS-MS and TEM results (83). This direct spectroscopic observation of β-sheet onset in oligomer growth is potentially a very important result and suggests that this type of investigation may be possible on systems of direct biological importance.…”
Section: Case 2: Peptide Assembly and The Amyloid Paradigmsupporting
confidence: 76%
See 2 more Smart Citations
“…Again space constraints prevent the details from being given here. It was found that β-sheet onset was spectroscopically observed for both VEALYL and YVEALL with onset at n = 4 extending to n = 9 (the largest oligomer studied) but no β-sheet absorptions were observed for VELYAL in accordance of expectations from both IMS-MS and TEM results (83). This direct spectroscopic observation of β-sheet onset in oligomer growth is potentially a very important result and suggests that this type of investigation may be possible on systems of direct biological importance.…”
Section: Case 2: Peptide Assembly and The Amyloid Paradigmsupporting
confidence: 76%
“…These results indicate the IMS-MS/FEL technique developed in the FHI in Berlin has a bright future in the analysis of the secondary structure of peptides and proteins and their assemblies adding a very powerful compliment to the ability of IMS-MS methods to directly measure tertiary structure of monomers and the quaternary structure of assemblies (36,83). …”
Section: Case 2: Peptide Assembly and The Amyloid Paradigmmentioning
confidence: 94%
See 1 more Smart Citation
“…[22][23][24] Further, IM-MS can be used to prepare samples for gas-phase IR spectroscopy. [25][26][27][28][29] Here ions are simultaneously mass-tocharge (m/z) selected by MS and specific oligomers are geometrical size selected by IMS. This is in contrast to experiments where only m/z selection is used which can suffer from signal overlap between a cluster and its larger counterpart, which, for example, have twice the mass and twice the charge.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the CO stretching vibration can be used as an effective marker for hydrogen bonding. 40,41 Two typical stretching bands appeared at 1743 and 1702 cm −1 , which are ascribed to the carbonyl C O stretching of the free and intramolecular H-bonded carboxylic acid. The disappearance of the former band and red shifts of the bands after sonication treatment reveal the breakage of weaker intramolecular interactions and formation of stronger intermolecular hydrogen bonding interactions.…”
Section: Resultsmentioning
confidence: 99%